Synthesis and Characterization of New Azopolyimides Derived from Azobenzene Tetracarboxylic Dianhydride - Kaniakumari, Devi; Rajendiran, T.V. (Asian Journal of Chemistry, 2010)
A monomer 3,3′4,4′-azobenzene tetracarboxylic dianhydride (ABTD) was synthesized and polyimides were prepared by polycondensation with aromatic diamines such as 2,2′-dimethoxy benzidine or orthodianisidine, 4,4′-diamino diphenylmethane, bis(p-aminocyclohexyl)- methane, 4,4′-diamino diphenyl ether, 4,4′-diamino benzanilide, 2,2- bis[4-[p-aminophenoxy]phenyl]propane and 4,4′-[1,4-phenylenediisopropylidene] bis aniline. The polyimides were prepared through three different methods (i) solution (ii) chemical and (iii) thermal imidization. The polymers were characterized by inherent viscosity, solubility, FT-IR, UV-visible, TGA and DTA studies. Activation energy has been calculated for the thermal degradation of the polyimides.